Cognitive Non-Orthogonal Multiple Access with Cooperative Relaying and Antenna Optimization using SADEA for Efficient Spectrum Sharing - Ntonya, Yohane Joseph; Musyoki, Stephen; Oduol, Vitalice (Engineering, Technology & Applied Science Research, 2025)
With the escalating need for efficient spectrum utilization, creative solutions are needed to enhance system performance in 5G wireless networks. This study presents a novel Cognitive Non-Orthogonal Multiple Access (C-NOMA) system coupled with cooperative relaying enhanced by Surrogate Model-Assisted Differential Evolution for Antenna Synthesis (SADEA) for antenna optimization. Latency, spectral efficiency, antenna parameters, and design protocols are studied to optimize the antenna and design protocol to reduce Outage Probability (OP) and Bit Error Rate (BER). The proposed method uses Probability Density Functions (PDF) for Rayleigh fading channels to derive system performance equations, evaluate metrics such as OP and BER, and finally perform MATLAB-based simulations. Robust signal processing is also ensured by Successive Interference Cancellation (SIC) and Channel State Information (CSI) techniques. The proposed SADEA-optimized system showed superior results to conventional methods, providing better BER and OP for communication reliability for 64 QAM and 128 QAM modulation schemes, for various SNR values and path numbers (L). The inclusion of SADEA in C-NOMA systems represents a promising avenue to achieve spectrum sharing and optimization of system performance in 5G networks.